Welcoming guests as a crucial part of good hospitality service - Kiurcheva, Yu. S. (ТДАТУ, 2020)
The hotel staff must demonstrate a positive attitude towards the client: show respect, conduct a polite conversation, in a friendly tone, without raising his voice, not show his displeasure, maintain restraint with absurd or aggressive clients, and demonstrate that they are concerned about his problem.
Keywords: hotel employee; hotel staff; follow the rules of etiquette